Sikap Bahasa Masyarakat Terhadap Penggunaan Bahasa Pertama Di Kecamatan Paleteang Kabupaten Pinrang - Rusdiana Rusdiana (Mathematics Education Study Program, 2025)
This study aims to: (1) reveal the language attitudes toward the use of the first language in Paleteang Subdistrict, Pinrang Regency, as seen from age, and (2) reveal the language attitudes toward the use of the first language in Paleteang Subdistrict, Pinrang Regency, as seen from gender. This type of research is a mixed-methods study, combining both quantitative and qualitative approaches. The population of this study consists of people living in Paleteang Subdistrict, Pinrang Regency. The sample for this study consists of 30 individuals. The sampling technique used was stratified random sampling, grouped into 5 age categories and 2 gender categories from the villages of Pacongang and Temmasarangnge. Data collection techniques included observation, questionnaires (surveys), and interviews, with data analysis using descriptive statistics and PawsStatistical analysis in the form of percentage data from each respondent’s answers on the language attitude scale. The results of the study indicate that: (1) The language attitudes (loyalty, pride, and awareness of norms) of the community toward the use of the first language in Paleteang Subdistrict, Pinrang Regency, based on age, are insufficient. This is due to the phenomenon in the minority community where individuals are neither loyal nor proud of their first language. The language attitude percentage scale is <50%, with a significant value of <0.05, (2) The language attitudes of the community toward the use of the first language in Paleteang Subdistrict, Pinrang Regency, based on gender, are adequate. This is reflected in the overall percentage result of the community's language attitude toward the use of the first language (Bugis or Makassar language), with a percentage greater than 50%. Both male and female attitudes are positive, with no significant difference in language attitudes (loyalty, pride, and awareness of norms) and a significant value of >0.05.